Potensi Ekstrak Beberapa Jenis Tanaman dalam Meningkatkan Stabilitas Oksidatif Minyak Kedelai - Dina Imama, Darus (Ma'soem University, 2025)
Soybean oil is one of the vegetable oils with a high content of unsaturated fatty acids; however, it is highly susceptible to oxidation, which can reduce its quality. Prevention is commonly carried out by adding synthetic antioxidants such as BHA, BHT, and TBHQ, which may pose potential adverse effects on health. The use of antioxidants derived from natural sources has therefore become increasingly preferred. Several plant extracts, including marigold flowers, eggplant peel, parsley leaves, olive leaves, jackfruit peel, as well as mixtures of pomegranate leaves, citrus leaves, and beet leaves, have been proven to enhance the oxidative stability of soybean oil by reducing peroxide values, limiting the formation of secondary oxidation compounds, and protecting unsaturated fatty acids. Innovative formulations such as nanoemulsions, acid hydrolysis, and encapsulation have also been shown to improve the efficiency and stability of bioactive compounds. The purpose of this article is to review recent studies on the utilization of plant extracts as natural antioxidant sources for addition to soybean oil. The findings indicate that extracts from various plant species have the potential to improve the oxidative stability of soybean oil.